Governance indicators for effective management of mangrove resources - Awang Marikan, Dayang Affizzah; Edman, Salbiah; Abu Bakar, Nor Afiza; Shuib, E. M. (Macrothink Institute, 2016)
Mangroves and marshes provide mutual benefits in terms of providing aquatic eco-systems. Swamp forests contribute a variety of services to carry out activities that depend on water resources such as agricultural production, fishing and tourism. Although the benefits are many, but the destruction of mangrove forests is alarming. A major reason for excessive depletion and conversion of wetland resources is often the failure to account adequately for their non market environmental values in developmental decision. The management role of the relevant agencies will only be effective pending supports by other stakeholders who may benefit directly or indirectly from the mangrove forest. Thus the approach should not only focus on the technical nor economic and socio political issues only but to reinforce the relationships of the players or actors who have interest in the domain of mangrove forest. This study aims to identify the process of governance and its effectiveness in managing the ecosystem and also assessing the role of mangrove forests towards local communities in Kuching Wetlands. Items are analyzed using factor analysis and the factor extraction leads to multiple regression method. The study distinguish that among the important factors in influencing the public perception of local governance mangrove forests in Kuching Wetlands, are community awareness, handling problems and conflict in the existing rules while other factors were not significant. However, most of the wetland local community does not contribute to ecotourism industry, even though they are aware of the importance if sustaining it. Thus the government can take opportunity to raise the awareness via the potential income that can be generated from eco tourism activities and realizing its importance of sustaining the natural resources.